This Is My Land - Erde, Tamara (France, Israel, Palestine, Poland : Iliade&Films, 2014)
The film follows several Israeli and Palestinian teachers during a school year and the way they teach their national history. Through exchanges and confrontations with students, debates about the Ministry of Education curricula, and teachers’ feedback, the film offers insight into the long lasting effect that the Israeli/Palestinian conflict transmits onto the young generations.
Verzio Film Festival Submission
Keywords: Documentary films